A note on surface grinding :|bstayblade, in the fully hardened and tempered condition UTS, 80 tons per sq. in., V.P.N 390. - Purcell, J. (College of Aeronautics, 1957)
SUMMARY The investigation carried out into surface grinding Stayblade shows that this material presents severe conditions to the grinding wheel, and the grinding wheel face is broken down fiarly quickly. The method described in C of A Note 38 for wheel and coolant selection and development enabled the total wheel face life to be improved from 0.105 cubic ins. to approximately 10.00 cubic ins, per redress with acceptable surface finish. The use of soluble typos of coolants would appear to be much less efficient than cutting or grinding oil coolants and the following combinations were found best:- Wheel:- Carborundum 7.D.A.60 I 5 IN BILT. Coolant:- Manchester Oil Refinery DOLPHIN MC OIL. Wheel life is 3.5 cubic ins. per redress for 7 ins. dia. by 1 in. wide wheel. The addition of 5% Wynns friction proofing fluid showed 200% increase in wheel face life with acceptable surface finish.